Character-Based Leadership Model in the Implementation of Character Education as an Effort to Overcome Radicalism - Lina Herlina; Sumarto Sumarto; Asep Suryana; Cepi Triatna; Diding Nurdin; Nurlaely Nurlaely (STAI Hubbulwathan Duri, 2022)
The government and schools have tried to strengthen the implementation of character education. However, there is no program to overcome radicalism. Everything returns to each individual, including the successful implementation of character education, which can at least minimize the influence of radicalism on the school environment. This study is intended to obtain a hypothetical model of Character-Based Leadership that can effectively affect the implementation of character education and efforts to combat radicalism. This research was conducted by studying phenomena that are part of the qualitative method. The object of this research is high school-level schools exposed to radicalism. The schools taken were two schools that had been exposed to radicalism. The subjects of this study were the principal, teachers, and students. Data collection was carried out by in-depth interview techniques, complemented by observation and document review. Data collection was carried out by several visits to the research field, cross-checking, primary data, and secondary data, complemented by literature studies and previous research. This study also meta-analyses several leadership models as a theoretical basis in producing character-based leadership components. The data processing of the results of this study was assisted by the NVIVO 12 Software to facilitate researchers in finding research results from so much field data. From the results of data analysis, researchers get many components of character values from character-based leadership, constructs, and frameworks in the implementation of character education. Finally, this study proposes the ideal character values possessed by someone who can be included in the category of character-based leadership who can become a leader in the implementation of character education and a leader who can prevent and overcome radicalism.